11(x-2)=6(x-3)11

Simple and best practice solution for 11(x-2)=6(x-3)11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11(x-2)=6(x-3)11 equation:



11(x-2)=6(x-3)11
We move all terms to the left:
11(x-2)-(6(x-3)11)=0
We multiply parentheses
11x-(6(x-3)11)-22=0
We calculate terms in parentheses: -(6(x-3)11), so:
6(x-3)11
We multiply parentheses
66x-198
Back to the equation:
-(66x-198)
We get rid of parentheses
11x-66x+198-22=0
We add all the numbers together, and all the variables
-55x+176=0
We move all terms containing x to the left, all other terms to the right
-55x=-176
x=-176/-55
x=3+1/5

See similar equations:

| 5x-(3x+7)=83 | | 5b+9=-b-3 | | 3z/10-2=9 | | 45=3(j-53) | | 4b-8=13b-4-9b | | 4+3/5x=230 | | 45=3(j–53) | | x/7+9=7 | | 14=4k+6 | | 14=4k=6 | | 2(2x-4)-3x=8-3(2-5x) | | 57=15-(12-6x) | | 5(7-x)=3x-8 | | 4a+4(3a+5)=84 | | -8r+7r=8-7r+4r | | 2(2x-4)-3x=8=3(2-5x) | | m/3-1=2m-7 | | 26/13=r/39 | | 10-2m=-2m+2m | | 6x+2=-2x-6 | | 5=3m-7 | | 28c+17-25c=38 | | X+35=3x+14 | | 75-4^3=y | | 2y=4(×-3)+9 | | 7x²+2=-19 | | 2x+5=3+2(x+1 | | 5n+3n+7=-43 | | -500+115x=2685 | | X+12=0.5(4x+12 | | 17−5x=20+3x | | 1/9y-4=-14 |

Equations solver categories